Studi Kasus Pengaruh Desain Visual (Warna dan Tipografi) terhadap Keterlibatan Mahasiswa dalam Pembelajaran Daring di Google Classroom - Muhammad Rizky; Marssellina Marssellina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of digital technology has driven a shift from face-to-face learning to online learning, particularly through e-learning platforms like Google Classroom. This change presents new challenges, one of which is maintaining student engagement throughout the learning process. This study aims to analyze the influence of visual design, specifically color and typography, on student engagement levels in online learning. The study used a quantitative approach with a case study design involving 60 students in the Islamic Library and Information Science Study Program at Imam Bonjol State Islamic University, Padang. Data were collected through a Likert-based questionnaire and analyzed using simple linear regression and descriptive analysis. The results indicate that color and typography have a positive and significant effect on student engagement, including focus, motivation, and participation in online classes. The implications of this study emphasize the importance of using attractive colors and easy-to-read typography to create a comfortable learning environment. Therefore, educators and e-learning developers are advised to pay attention to visual elements when developing digital learning materials to make the learning experience more interactive and effective.